1996
DOI: 10.1121/1.416018
|View full text |Cite
|
Sign up to set email alerts
|

Electroseismic wave properties

Abstract: In a porous material saturated by a fluid electrolyte, mechanical and electromagnetic disturbances are coupled. The coupling is due to an excess of electrolyte ions that exist in a fluid layer near the grain surfaces within the material; i.e., the coupling is electrokinetic in nature. The governing equations controlling the coupled electromagnetic-seismic (or ‘‘electroseismic’’) wave propagation are presented for a general anisotropic and heterogeneous porous material. Uniqueness is derived as well as the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
326
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(334 citation statements)
references
References 0 publications
7
326
1
Order By: Relevance
“…Thus, for dipoles contained within a single layer it seems reasonable that the signals may be approximately modelled as if they were in unbounded homogeneous media. Plane wave solutions for fully coupled seismic and electromagnetic waves in homogeneous, poroelastic media have been derived by Pride and Haartsen [1996]. Garambois and Dietrich [2001] reported that co-seismic seismoelectric signal strengths measured at surface were consistent with predictions based on a low frequency form of that theory.…”
Section: Validation Of a Theoretical Modelmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, for dipoles contained within a single layer it seems reasonable that the signals may be approximately modelled as if they were in unbounded homogeneous media. Plane wave solutions for fully coupled seismic and electromagnetic waves in homogeneous, poroelastic media have been derived by Pride and Haartsen [1996]. Garambois and Dietrich [2001] reported that co-seismic seismoelectric signal strengths measured at surface were consistent with predictions based on a low frequency form of that theory.…”
Section: Validation Of a Theoretical Modelmentioning
confidence: 64%
“…In this case, we compare our borehole measurements to an alternative model, developed by Neev and Yeatts [1989] which has received less attention in the literature. The model is simpler and less general than that of Pride and Haartsen [1996] in that it ignores electromagnetic effects and any frequency dependence of physical properties. Plane wave solutions for seismoelectric effects expected to accompany seismic Pwaves were instead derived by treating the problem as quasi-static and modifying Biot's poroelastic equations of motion to account for electric forces that would arise due to electrokinetic coupling.…”
Section: Validation Of a Theoretical Modelmentioning
confidence: 99%
“…[21] In a uniform material, the fluid accumulations and volume dilatations in the slow wave are exactly related as [e.g., Pride, 2004;Pride and Haartsen, 1996] …”
Section: Fluid-pressure Variationsmentioning
confidence: 99%
“…In order to simplify this problem, we use the reciprocity theorem (eq. 9) (Pride and Haartsen, 1996;Sahay, 2001), and assume that the average force F 1 acting on the porous medium and fluid force F 2 are similar (Garambois and Dietrich, 2002). This simplification allows us to drop the j index of the Green's functions (eq.…”
Section: Coupled Second-order Equations For Plane P-sv Wavesmentioning
confidence: 99%